“Soft” Alkali Bromide and Iodide Fluxes for Crystal Growth - Klepov, Vladislav V.; Juillerat, Christian A.; Pace, Kristen A.; Morrison, Gregory; zur Loye, Hans-Conrad (Frontiers in Chemistry, 2020)
In this review we discuss general trends in the use of alkali bromide and iodide (ABI) fluxes for exploratory crystal growth. The ABI fluxes are ionic solution fluxes at moderate to high temperatures, 207 – 1300 °C, which offer a good degree of flexibility in the selection of the temperature profile and solubility. Although their main use is to dissolve and recrystallize “soft” species such as chalcogenides, many compositions with “hard” anions, including oxides and nitrides, have been obtained from the ABI fluxes, highlighting their unique versatility. ABI fluxes can serve to provide a reaction and crystallization medium for different types of starting materials, mostly the elemental and binary compounds. As the use of alkali halide fluxes creates an excess of the alkali cations, these fluxes are often reactive, incorporating one of its components to the final compositions, although some examples of non-reactive ABI fluxes are known.